Autism Spectrum Disorder (Advancements in Homeopathic Research, 2022)
This rendering of mine is about restoring back the normal, healthy, colourful life to the autistic children. Based on my meticulous and conscientious studying of all available hypotheses and contradictions and some satisfactory result after applying homeopathic medicines in this cases – I have rendered this.
Keywords: Autism Spectrum; homeopathic medicines; behaviour